The J/ψΦ decay channel of the Y(4140) Molecular State - Albuquerque, R. M. [UNESP]; Matheus, R. D. [UNESP] (Elsevier, 2015)
Using the QCD sum rule approach we study the Y(4140) state assuming that it can be described by a D* sD* s molecular state with JPC = 0++ quantum numbers. We evaluate the decay width into the channel Y J/ψΦ and we find the value ΓY→ J/ψΦ≃ (0.34 ± 0.11) MeV, which is much smaller than the total experimental width Γ ≃ (20 ± 8) MeV. However, considering the experimental upper limits for the decay of the Y(4140) into di-photons, Γ γγ×Β[ΓY→J/ψΦ]> 41 eV, such a scalar molecule can be a good candidate to explain the possible exotic structure of the Y(4140) state. © 2016.
Keywords: Exotic mesons and heavy quarkonia; Molecular states; QCD spectral sum rules